On one generalization of Wronskian - Kirjackis, Eduardas (Lietuvos matematikos rinkinys, 2007)
In this article the properties of the specially introduced determinant, elements of which are the divideddifferences in different orders are studied. The close connection of this determinant with the Chebyshevsystem and the ordinary differential equation is indicated.
Keywords: determinant; wronskian; divided differences; Chebyshev system